THE DIFFERENCE OF THE EFFECTIVENESS OF INTERVENTION MUSCLE ENERGY TECHNIQUE AND INTERVENTION ACTIVE ISOLATED STRETCHING IN IMPROVING HAMSTRING MUSCLES FLEXIBILITY OF FOOTBALL PLAYERS IN SMAN 1 SEMARAPURA - Puspaningsih, Intan Ayu; Andayani, Nopi; Primayanti, I Dewa Ayu Inten Dwi; Sutadarma, I Wayan Gede (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 1 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i01.p06, 2018)
ABSTRACT The excessive use of the hamstring muscle in footballplayers as the main cause of tension on the muscle. Good flexibility of hamstring muscle can support the quality of the players. The purpose of this study was to prove the different effectiveness of intervention muscle energy technique and active isolated stretching in improving hamstring muscles flexibility of football players. This research was used the design of randomized pre and post test two group design. The sampling technique used is simple random sampling. There are 22 people as the samples were divided into 2 groups: group I( muscle energy technique) . and group II( active isolated stretching). Each group consists of 11 people. The result of the research showed that the increased flexibility of hamstring muscle in group I of 12,4 and in group II of 7,0. The result of paired sampel t-test showed the value of p=0,00(p<0,05) in group I and value of p=0,00(p<0,05)in group II. On different average test using independent test show that contained significant increase between group I and group IIin which p=0,00(p=0,05). With the percentage of 51,5% in group I and 26,0% in group II. Based on the result can be concluded that intervention muscle energy technique more effective in increasing the hamstring muscles flexibility rather that intervention active isolated stretching of football players. Keywords: muscle energy technique, active isolated stretching, sit and reach test, hamstring muscles flexibility.